2020
DOI: 10.2147/idr.s273989
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vitro Activity of Ceftazidime-Avibactam and Aztreonam-Avibactam Against Carbapenem-resistant <em>Enterobacteriaceae</em> Isolates Collected from Three Secondary Hospitals in Southwest China Between 2018 and 2019</p>

Abstract: To assess the antimicrobial activities of ceftazidime/avibactam (CAZ/AVI) and aztreonam/avibactam (ATM/AVI) against carbapenem-resistant Enterobacteriaceae (CRE) isolates collected from three secondary hospitals in Southwest China between 2018 and 2019. Materials and Methods: A total of 120 unique CRE clinical isolates were collected and carbapenemase genes were detected using PCR. Antimicrobial susceptibility was determined using standard broth microdilution method and the results were interpreted according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
6
14
1
4
Order By: Relevance
“…In regions with a high susceptible rate of CZA, KPCs was the major epidemic genotype. 15 , 34 , 35 Whereas, in the study of the Arabian Peninsula a susceptible rate of CZA (53.3%) against CRE was observed and OXA was the most common CRE genotype similar to our result. 33 Hence, in a KPC epidemic region, CZA are recommended in some guidelines as the first-line antimicrobial agent against CRE.…”
Section: Discussionsupporting
confidence: 90%
“…In regions with a high susceptible rate of CZA, KPCs was the major epidemic genotype. 15 , 34 , 35 Whereas, in the study of the Arabian Peninsula a susceptible rate of CZA (53.3%) against CRE was observed and OXA was the most common CRE genotype similar to our result. 33 Hence, in a KPC epidemic region, CZA are recommended in some guidelines as the first-line antimicrobial agent against CRE.…”
Section: Discussionsupporting
confidence: 90%
“…A series of molecular epidemiology studies on CRE in China have shown that the outbreaks caused by KPC-2-producing K. pneumoniae in these regions were due to the spread of the predominant clone ST11, which is a variant of international clone ST258. [26][27][28][29][30] ST258 is strongly associated with KPC production and multidrug resistance, but it may have inherent traits which are responsible for its high rate of transmissibility that results from two distinct genetic clades with a hot spot for DNA recombination. 31 There are some limitations of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, for example high rates of CZA resistance were reported from UAE (55%) [23] and Arabian Peninsula (47%) [24]. These were higher than rates reported from USA (range between 0.3% and 3.6%) [19,20,21] and China (25%) [16,22].…”
Section: Discussionmentioning
confidence: 92%